PENGARUH KUALITAS KEHIDUPAN KERJA DAN KEPERCAYAAN DIRI DAN BUDAYA PERUSAHAAN TERHADAP PENINGKATAN KINERJA KARYAWAN - Muhammad Rafif Akbarsyah; Anra Tinambunan; Muhammad Zein Erian (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The purpose of this study is to determine whether the quality of work life, self-confidence and corporate culture can improve an employee's performance. The research method used is literature study, where information is collected from several reliable sources. The results of the study show that a good quality of work life can improve employee performance by creating a healthy and comfortable work environment. This can motivate employees to work more productively and creatively in their tasks. In addition, high employee selfconfidence can have a positive impact on their performance. Employees who are confident in their abilities are more likely to take initiative and take risks to achieve better results. Good corporate culture can also affect employee performance. A positive corporate culture can create a harmonious and supportive work environment that can motivate employees to work better and achieve more satisfying results. In short, it can be said that the quality of work life, self-confidence and corporate culture play an important role in improving employee performance. Therefore, companies must provide a healthy and comfortable work environment, provide opportunities for employees to develop themselves and pay attention to the values and norms contained in the corporate culture. In this way, employee performance can improve and better results can be achieved.